International Copyright Protection: The State Of The Malaysian Law, In Perspective - Reiss, Seth (Journal of Malaysian and Comparative Law, 1986)
The Supreme Court of Malaysia, through its decision in Foo Loke Ying & Anor v Television Broadcasts Ltd & Ors appears to have settled the issue of whether a foreign national who first publishes in Malaysia may claim protection under Malaysia’s Copyright Act, 1969.